Selected Papers from 2018 IEEE International Conference on High Voltage Engineering (ICHVE 2018) - Fofana, Issouf; Gonos, Ioannis F. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The 2018 IEEE International Conference on High Voltage Engineering (ICHVE 2018) was held on 10-13 September 2018 in Athens, Greece, organized by the National Technical University of Athens, Greece, and endorsed by the IEEE Dielectrics and Electrical Insulation Society. This conference has attracted a great deal of attention from international researchers in the field of high voltage engineering. This conference provided not only an excellent platform to share knowledge and experiences on high voltage engineering, but also the opportunity to present the latest achievements and different emerging challenges in power engineering, including topics related to ultra-high voltage, smart grids, and new insulation materials and their dielectric properties.